Biology of the acarus Brevipalpus phoenicis in citrus - Chiavegato, Luiz Gonzaga (Pesquisa Agropecuaria Brasileira, 2014)
The biology of the leprosis mites B. phoenicis was studied on 'Valencia' and 'Pera Rio' oranges. The work was carried out under laboratory conditions at 20, 25 and 30°C ± 1°C, 60 ± 10 R.H. and 14 hr. photoperiod. The length of incubation period, the duration of each stage, larval, nymphal, the stages of pre-oviposition, oviposition, the total number of eggs per female and the adult longevity were determined in this work.